Factors Influence Brand Loyalty in Shoe Products in Batam City - Azwin Handoko; Suyono Saputra (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This study aims to determine the factors that influence shoe brand loyalty in Batam City. The independent variables used include brand experience, brand personality, corporate social responsibility, consumer involvement, and perception mediated by brand trust. The research methodology used is quantitative research methodology. The data used is primary from the survey results using an online questionnaire. The number of samples studied was 400 respondents. Sampling using purposive sampling technique, the samples were selected based on certain considerations. Respondents who were sampled were residents of Batam City who often wore shoes. The analysis method used is the Structural Equation Model (SEM) method using SmartPLS 3 software. The results of this study found that brand experience, corporate social responsibility, brand involvement, and perceived value have a significant and positive effect on brand trust. Brand trust plays a mediating role between the independent variables and brand loyalty. A mediating effect on brand trust was found. Brand experience, corporate social responsibility, brand involvement, and perceived value have an indirect effect on brand loyalty mediated by brand trust. Brand trust has a significant and positive effect on brand loyalty.